Pengaruh Kualitas Pelayanan, Kepercayaan, Dan Keamanan Terhadap Minat Beli Ulang Konsumen Di LAZADA - Muhammad Yusuf Romadhoni; Susanto Susanto; Putri Dwi Cahyani (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
In this era of globalization, internet technology is growing very rapidly an can be used to run a business through an application called e-commerce. On of the e-commerce that has been in business for a long time is Lazada. Lazada sustainability to compete with other e-commerce is influenced by consumer repurchase intention. The factors that determine the high an low influenced of repurchase intention are service quality, trust, and security. This study involves foot four variables, namely service quality, trustworthiness, and security as independent variables and repurchase interest as the dependent variable. For the population in this study, the students of the Faculty of Economics, UST, were taken as a sample of 105 respondents. The results of the research conducted show that service quality, trust, and security simultaneously (simultaneously) have a significant effect on consumer repurchase interest at Lazada, service quality has a significant effect on consumer repurchase interest at Lazada, trust has a significant effect on consumer repurchase interest. in Lazada, security has a significant effect on consumer repurchase interest in Lazada. Keywords: Service Quality, Trust, Security, Repurchase Intention